Femmes du Tiers-Monde : des documentations spécialisées [3] - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
IBISCUSUne bibliographie sur Femmes et Développement est parue en septembre 1992